A greater love Prince Charles's twenty-year affair with Camilla Parker Bowles - Wilson, Christopher 1946- (Morrow, 1994)
Documenting the relationship between Prince Charles and Mrs. Camilla Parker Bowles, an expose tells the story of the long-lasting affair, and includes background information on Mrs. Bowles.
Keywords: Camilla <Duchess of Cornwall, 1947->; Charles <Prince of Wales, 1948-> -- Relations with women; Charles <Prince of Wales>; Camilla -- Großbritannien, Königin -- 1947-; Charles -- III. -- Großbritannien, König -- 1948-; . -- Princes and princesses -- Biography; Princes -- Great Britain -- Biography; Großbritannien; Biografie